Green Accounting: An Environmental Pollution Prevention Effort to Support Business Continuity - I Gusti Agung Prama Yoga; Ida I Dewa Ayu Manik Sastri (Jurnal Ekonomi dan Bisnis Jagaditha, 2020)
Green accounting has appeared as an accounting era putting forward the environmental factors as the impact of the business sustainability principle that must be maintained by an entity. This study aims to examine the environmental accounting treatment that has been applied by PT Quarzia Batik Baliand to determine the implementation of Green Accounting in supporting the business continuity of PT Quarzia Batik Bali. Business continuity acts as an economic principle, while environmental sustainability represents the social and environmental impacts generated by economic actors. These two aspects must be reconciled as their crucial nature is long-term. This study is design by using the descriptive-interpretive qualitative analysis method, which is a tool to analyse the information and data collected by interpreting the data based on the actor’s perspective. Systematically, this data processing and analysis method consists of three concurrent flows of analysis activities, such as data collection through interviews and questionnaires, data reduction, and drawing conclusions. The results showed that PT Quarzia Batik Bali has anticipated the environmental pollution due to dyed waste produced from the garment industry using environmentally-friendly dyes and provides several storage tanks to recycle waste so it remains ready to be disposed of on earth. However, in the financial report the processing cost has not been presented separately as an anticipated cost of environmental pollution.